GAGASAN INTEGRASI ZAKAT DAN PAJAK PERSPEKTIF MAQASHID SYARIAH: PENDEKATAN SISTEM JASSER AUDA - Nikmah, Roykhatun (Filantropi : Jurnal Manajemen Zakat dan Wakaf, 2021)
Several kinds of literature have tried to formulate the concept of zakat and tax integration or the idea that tax is a form of zakat, such as Masdar Farid Mas'udi's view. Zakat which has vertical as well as horizontal dimensions has great potential in realizing the welfare and benefit which is the goal of shari'at (maqashid syari'ah), as well as the role of taxes. This paper explains the discourse of integrating zakat and tax as a new concept in optimizing the management of zakat and tax funds in building social welfare, alleviating poverty, and realizing Sustainable Development Goals (SDGs). The concept of zakat and tax integration will be reviewed based on the contemporary maqashid sharia theory initiated by Jasser with a systems approach. maqashid of classical sharia which tends to prioritize the benefit of the individual is expanded to include the benefit of society. By integrating zakat and taxes in a government policy, the benefit of society, in general, will be realized, the purpose of Islamic law is no longer just safeguarding and preservation but shifting towards development. Beberapa literatur telah mencoba memformulasikan konsep integrasi zakat dan pajak atau gagasan yang mengatakan pajak merupakan bentuk dari zakat seperti pandangan Masdar Farid Mas'udi. Zakat  yang memiliki dimensi vertikal dan juga horizontal memiliki potensi besar dalam mewujudkan kesejahteraan dan kemaslahatan yang merupakan tujuan dari syariat (maqashid syariah), begitu pula dengan peran pajak. Tulisan ini menjelaskan wacana integrasi zakat dan pajak sebagai konsep baru dalam mengoptimalkan pengelolaan dana zakat dan pajak dalam membangun kesejahteraan sosial, mengentaskan kemiskinan dan mewujudkan Sustainable Development Goals (SDGs). Konsep integrasi zakat dan pajak akan ditinjau berdasarkan teori maqashid syariah kontemporer yang digagas oleh Jasser dengan pendekatan sistem. maqashid syariah klasik yang cenderung memprioritaskan kemaslahatan individu diperluas dengan cakupan kemaslahatan masyarakat. Dengan mengintegrasikan zakat dan pajak dalam suatu kebijakan pemerintah maka akan terwujud kemaslahatan masyarakat secara umum, tujuan hukum Islam tidak lagi sekedar penjagaan dan pelestarian tapi bergeser menuju pengembangan.